Gastric metastasis from breast cancer presenting as dysphagia. Issue 3 (17th March 2022) - Fousekis, Fotios S; Tepelenis, Kostas; Stefanou, Stefanos K; Stefanou, Christos K; Pappas-Gogos, George; Theopistos, Vasileios; Evangelou, Zoi; Mauri, Davide; Christodoulou, Dimitrios K
Abstract: Gastric metastasis from breast cancer occurs infrequently and causes non-specific symptoms, usually attributed to the underlying disease. Furthermore, endoscopic findings are almost identical to primary gastric cancer, making the immunohistochemical examination of biopsies necessary for diagnosis. We present the case of a 64-year-old woman who was diagnosed with lobular breast cancer 3 years ago and received chemotherapy with evidence of remission. The patient presented with dyspepsia and progressive dysphagia for the last 6 months, not responsive to PPI treatment. Upper endoscopy revealed partial occlusion of the cardio-esophageal junction and thickened gastric folds resembling linitis plastica. However, immunohistochemical analysis of endoscopic biopsies showed infiltration of gastric mucosa by lobular breast cancer cells, making the diagnosis of gastric metastasis. Therefore, clinicians' awareness of possible gastric metastasis is warranted in patients with a history of advanced breast cancer and severe gastric symptoms.